ANALISIS PERAN STRATEGIK MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS KERJA KARYAWAN - Indra Brata Manggala, Rieki; Kartika, Windy; Mega, Aryanti (PPM Sdirjianbang Akademi Militer, 2024)
Human resources have a very important role in an organization. The success of an organization in resolving the challenges that come is not only determined by the behavior of employees who are assigned according to their job description. This research uses qualitative data with a literature review research method. The results of this research state that the role of human resources is to be committed to managing human resources through policies and skills development programs that are implemented periodically for company employees at all levels. The various policies and programs implemented aim to produce human resources with high quality and work ethic so that they will have a positive influence on the company's development in carrying out business activities while creating sustainable values. The HR management functions carried out include various processes starting from recruitment and selection, training and development, performance evaluation, as well as ensuring the creation of a safe and comfortable work environment for all employees. Keywords: Strategic Management, Human Resources, Work Quality, Employees